Termorregulação da abelha mamangava de grande porte Xylocopa frontalis nos neotrópicos diante das mudanças climáticas - Silva, Felipe Jackson de Farias (2020)
There is evidence that climate change, particularly global warming, can alter the ideal ecological conditions for the survival of many pollinator species, especially small bees that reside in temperate environments. However, little is known how the rise in the average ambient temperature could affect the survival of large bees in tropical regions of the planet. In the present work, we investigated the thermoregulation process of the large carpenter bee Xylocopa frontalis nesting freely in rational nests that allow the direct measurement of its body temperature while performing the various activities necessary for its survival and reproduction in a tropical environment. The results showed that this species uses thermoregulation strategies such as heat loss by convection, evaporative cooling by dehydrating the nectar, and avoid foraging during the hottest times of the day, to avoid overheating and thrive in the studied area. However, it can be concluded that the areas where these bees live are on the threshold of the ecological conditions necessary for the survival of these bees and future climate changes, among them mainly the rise in environmental temperatures, can represent a serious risk for the survival of X. frontalis and other similar tropical species